Electrophysiological Correlates of Language Processing in Schizotypal Personality Disorder - Niznikiewicz, Margaret A. (1999)
OBJECTIVE: This study examined whether the electrophysiological correlates of language processing found previously to be abnormal in schizophrenia are also abnormal in schizotypal individuals. The authors used the N400 component to evaluate language dysfunction in schizotypal individuals. METHOD: Event-related potentials were recorded in 16 comparison subjects and 17 schizotypal individuals (who met full DSM-III-R criteria) to sentences presented both visually and aurally; half of the sentences ended with an expected word completion (congruent condition), and the other half ended with an unexpected word completion (incongruent condition). RESULTS: In the congruent condition, the N400 amplitude was more negative in individuals with schizotypal personality disorder than in comparison subjects in both the visual and auditory modalities. In addition, in the visual modality, the N400 latency was prolonged in the individuals with schizotypal personality disorder. CONCLUSIONS: The N400 was found to be abnormal in the individuals with schizotypal personality disorder relative to comparison subjects. The abnormality was similar to the abnormality the authors’ laboratory reported earlier in schizophrenic subjects, in which the N400 amplitude was found to be more negative in both congruent and incongruent sentence completions. The N400 abnormality is consistent with the inefficient use of context.